2008
DOI: 10.1007/s00280-008-0755-1
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the interactions between the chemotherapeutic agent eribulin mesylate (E7389) and human CYP3A4

Abstract: Eribulin was predominantly metabolized by CYP3A4. Although eribulin competitively inhibited the testosterone 6beta-hydroxylation, nifedipine dehydration, and R-warfarin 10-hydroxylation activities of rCYP3A4, it did not induce or inhibit hepatic CYP3A4 activity at clinically relevant concentrations. As eribulin does not appear to affect the metabolism of other therapeutic agents by CYP3A4, our data suggest that eribulin would not be expected to inhibit the metabolism of concurrently administered drugs that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Metabolites MF2 and MF3, with molecular masses of eribulin ϩ 16, may be products of hydroxylation. Eribulin metabolites with the same molecular masses were reported previously by Zhang et al (2008) in an in vitro study with human liver microsomes. That study showed that ID, identification; n, number of patients for which this metabolite was observed in urine/feces; ⌬ppm, deviation of accurate mass from theoretical mass in parts-per-million; unk, unknown.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Metabolites MF2 and MF3, with molecular masses of eribulin ϩ 16, may be products of hydroxylation. Eribulin metabolites with the same molecular masses were reported previously by Zhang et al (2008) in an in vitro study with human liver microsomes. That study showed that ID, identification; n, number of patients for which this metabolite was observed in urine/feces; ⌬ppm, deviation of accurate mass from theoretical mass in parts-per-million; unk, unknown.…”
Section: Discussionmentioning
confidence: 72%
“…Preclinical studies showed that eribulin is metabolized predominantly by CYP3A4 (Zhang et al, 2008). In clinical studies, eribulin was found to be minimally eliminated in its unchanged form in urine (Goel et al, 2009;Tan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Eribulin also had a wide therapeutic window; specifically, eribulin appeared to cause less neurotoxicity, manifest as less functional and morphological damage, than paclitaxel in mice. 33 Preclinical pharmacokinetic studies in rats showed extensive tissue distribution, and a prolonged elimination half-life, 34 with eribulin predominantly metabolized by cytochrome P450 (CYP) 3A4 35 and eliminated principally in the feces.…”
Section: 25mentioning
confidence: 99%
“…Although eribulin is metabolized principally by hepatic CYP3A4, it appears not to cause relevant induction or inhibition of CYP3A4, so drug-drug interactions would not be expected. 35 A population pharmacokinetic-pharmacodynamic analysis of patients in the Phase I and II studies showed that eribulin clearance was affected by body weight, serum albumin, alkaline phosphatase, and bilirubin. 41 Interestingly, fatigue appeared not to be influenced by exposure to eribulin; neuropathy was, by contrast, related to cumulative eribulin exposure.…”
Section: -39mentioning
confidence: 99%